Reviewing The Benefits of Health Workforce Stability - Buchan James (BMC, 2010)
Abstract This paper examines the issue of workforce stability and turnover in the context of policy attempts to improve retention of health workers. The paper argues that there are significant benefits to supporting policy makers and managers to develop a broader perspective of workforce stability and methods of monitoring it. The objective of the paper is to contribute to developing a better understanding of workforce stability as a major aspect of the overall policy goal of improved retention of health workers. The paper examines some of the limited research on the complex interaction between staff turnover and organisational performance or quality of care in the health sector, provides details and examples of the measurement of staff turnover and stability, and illustrates an approach to costing staff turnover. The paper concludes by advocating that these types of assessment can be valuable to managers and policy makers as they examine which policies may be effective in improving stability and retention, by reducing turnover. They can also be used as part of advocacy for the use of new retention measures. The very action of setting up a local working group to assess the costs of turnover can in itself give managers and staff a greater insight into the negative impacts of turnover, and can encourage them to work together to identify and implement stability measures.